SAT0165 Tofacitinib versus Biologic Treatments in Moderate To Severe Rheumatoid Arthritis Patients Who Have Had An Inadequate Response To Nonbiologic Dmards: Systematic Literature Review and Network Meta-Analysis. (15th July 2016) - Bergrath, E.; Wallenstein, G.; Gerbert, R.; Gruben, D.; Makin, C.
Abstract : Background: Rheumatoid Arthritis (RA) patients who are intolerant, show an inadequate response, or experience moderate/high disease activity despite traditional, non-biologic disease-modifying antirheumatic drugs (inadequate response [DMARD-IR] or second-line therapy patients) are often treated with a biologic agent (or "novel DMARDs") in Europe. Other treatments of interest, such as Janus kinase (JAK) inhibitors (a new class of DMARDs) are currently in development. Tofacitinib is an oral JAK inhibitor for the treatment of RA. Objectives: The overall objective of this study was to compare the efficacy, and safety/tolerability of tofacitinib as monotherapy and combined with a DMARD relative to biological DMARDs (bDMARDs) and other novel DMARDs currently approved or being considered for approval by the European Medicines Agency (EMA) for second-line moderate-to-severe RA patients by means of a systematic literature review (SLR) and network meta-analysis (NMA) of randomized clinical trial (RCT) evidence. Methods: MEDLINE®, EMBASE®, and Cochrane Central Registry of Controlled Trials databases were searched simultaneously to identify RCTs published in English between 1990 and March 2015. Population of interest included adults with moderate to severe RA who had responded inadequately or failed treatment with at least one traditional, non-biological DMARD. Treatments approved by the EMA for moderate-to-severe RA and investigational therapies were of interest and included: abatacept, adalimumab, anakinra, certolizumab pegol, etanercept, golimumab, infliximab, tocilizumab, baricitinib (investigational), and tofacitinib (investigational). Outcomes of interest were: American College of Rheumatology (ACR) response criteria (20/50/70), change from baseline in the Health assessment questionnaire (HAQ-DI), the Disease activity score (DAS-28) (change from baseline and categorical), and safety outcomes. Bayesian NMA models were simultaneously synthesized to obtain treatment effects for the outcomes of interest. Results: 68 full-text articles and 11 conference abstracts corresponding to 45 RCTs were identified, the majority of which demonstrated a low risk of bias. Based on evidence synthesis of monotherapies, tofacitinib 5 mg twice daily (BID) and 10 mg BID monotherapy exhibited comparable efficacy, and safety/tolerability to other monotherapies. Based on evidence synthesis of combination therapies, tofacitinib 5 mg BID and 10 mg BID + DMARDs or methotrexate (MTX) were mostly comparable to other combination therapies in terms of efficacy based on DAS28 and ACR. In terms of safety, tofacitinib 5 mg BID + MTX or DMARDs was mostly comparable to other combination therapies, but less favorable versus some (with respect to withdrawals, infections, serious adverse events), and tofacitinib 10 mg BID + MTX or DMARDs was comparable to most, but less favorable in terms of withdrawals versus a few treatments. Conclusions: Tofacitinib 5 mg BID and 10 mg BID, either as monotherapy or combined with DMARDs or MTX is comparable to other monotherapies and combination therapies respectively, based upon DAS28 and ACR response criteria. While monotherapies were also comparable in terms of safety, further research is recommended to firmly establish the comparative safety of the combination therapies. Disclosure of Interest: E. Bergrath Consultant for: Paid consultant for Pfizer, G. Wallenstein: None declared, R. Gerbert: None declared, D. Gruben: None declared, C. Makin: None declared